Design, synthesis, and biological evaluation of novel covalent inhibitors targeting focal adhesion kinase. (15th December 2021) - Chen, Tao; Liu, Yan; Shi, Mingsong; Tang, Minghai; Si, Wenting; Yuan, Xue; Wen, Yi; Chen, Lijuan
Graphical abstract: Highlights: 41 novel FAK covalent inhibitors were synthesized. Compound 11w displayed highest inhibition of FAK and tumor cells. 11w inhibited the clone formation and migration of tumor cells, inducing apoptosis. 11w covalently inhibited the autophosphorylation of FAK in a dose-dependent manner. 11w showed adequate oral bioavailability and significant antitumor efficacy in vivo . Abstract: Forty-one new focal adhesion kinase (FAK) covalent inhibitors were designed and synthesized based on FAK inhibitor TAE226. Compound 11w displayed the highest inhibition of FAK with an IC50 value of 35 nM and exhibited potent anticancer activity against Hela, HCT116 and MDA-MB-231 cell lines with IC50 values of 0.41, 0.01 and 0.11 μM respectively, compared to TAE226 (2.68, 0.64 and 4.19 μM respectively). 11w also inhibited the clone formation and migration of HCT-116 cells and stimulated cell cycle arrest in the G2 /M phase, inducing tumor cell apoptosis. Compound 11w formed a covalent bond with the Cys427 residue of FAK in a docking model, inhibiting the autophosphorylation of FAK and downstream proteins in a dose-dependent manner. Moreover, 11w showed adequate oral bioavailability of 21.02%. A 74.20% inhibition of tumor growth in the HCT116 xenograft model was also observed. These data indicate that 11w is a promising covalent inhibitor of FAK.